Effects of covid-19 outbreak lockdown on food supply in Ilorin South Local Government Area, Kwara State, Nigeria - Ibrahim Ologele; Bushrah Daud; Taofeekat Omotoyosi Hussain; Mariam Omowumi Isiaq (Universitas PGRI Madiun, 2023)
The study investigated the effects of covid-19 outbreak lockdown on food supply in Ilorin South Local Government Area, kwara State. The purpose of this study was to investigate if: (i) covid-19 lockdown will change the purchase pattern of food supply in Ilorin South Local Government Area, kwara State, (ii) covid-19 lockdown will reduce the amount of nutritious food consume by people in Ilorin South Local Government Area, kwara State. A descriptive research of the survey type was adopted for the study. The population of the study comprised of residents in Ilorin South Local Government Area. Multi-stage sampling technique was used to select two hundred and twenty-one (221) respondents used for the study.. The research instrument used for this study was a questionnaire. The instrument was validated by three experts in the related field. The reliability of the instrument established through test-retest and result of 0.87r was obtained using Pearson Product Moment Correlation. The findings of the study revealed that, Covid-19 lockdown change the purchase patterns of food supply in Ilorin South Local Government Area, Kwara, and Covid-19 lockdown reduce the amount of nutritious food consume by people in Ilorin South Local Government Area, Kwara State. Based on the findings of the study, it was concluded that, Covid-19 lockdown change the purchase patterns of food, and reduce the amount of nutritious food consume by people in the study area. Therefore, it was recommended that health educators’ practitioners should create more awareness on healthy eating and disseminate information about effective protection measures while shopping.